A consolidação institucional da Ordem dos Advogados do Brasil: prerrogativas conquistadas desde sua fundação até a Constituição de 1988 - Souza, Lucilly Maria Caetano de (2018)
This research aims to analyse the history of institutionalization of the Brazilian Bar Association (OAB). Although it was created as a professional organization, the Order has managed, over time, to accumulate institutional prerogatives to the corporate functions of class, with strong action in the political and social scene, as well as in the constitutional scope. The wide temporal gap adopted in this research (1930 to 1988) is precisely to understand the ‘institutionalization’ of the organization, as well as the consolidation of a new democratic State of Law, with the promulgation of the Federal Constitution in 1988. It adopts the theoretical perspective of the historical institutionalism because it is the theoretical line that provides the best instruments for the understanding of organizations that acquire institutional characteristics. The Order has become an institution of a hybrid nature. Created to represent a professional category, it began to act and influence at varying levels of power. These characteristics contributed to her gaining prominence in the different political periods of Brazilian history. The OAB became an even more influential actor when acquiring constitutional prerogatives, including its participation and intervention in the organization of political power. The qualitative methodology was used based on extensive literature and documentary research, including legislation and other legal documents issued during the established period of time.